The Influence of Qris Use on Shopping Behavior in Faculty Economics and Business Students Swadaya Gunung Jati University - Rosmayanti, Indah Fatma; Sakinah, Firna Octavia; Nursyafikha, Indah; Riyanto, Aris (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The development of digital payment systems has contributed to changes in students’ shopping behavior, particularly through the use of the Quick Response Code Indonesian Standard (QRIS). This study aims to explore the effect of QRIS usage on the shopping behavior of students at the Faculty of Economics and Business, Universitas Swadaya Gunung Jati (FEB UGJ). This research employs a qualitative approach using semi structured interviews with nine FEB UGJ students selected through purposive sampling. The respondents were categorized into three groups based on the intensity of QRIS usage, namely frequent users, moderate users, and infrequent users, as all respondents were familiar with and had experience using QRIS. The findings indicate that QRIS usage has varying effects on students’ shopping behavior. Students categorized as frequent users tend to experience an increase in shopping frequency and expenditure due to the convenience of transactions and the availability of promotions such as cashback and discounts. Moderate users utilize QRIS situationally, particularly when they do not carry cash or when promotional offers are available, with a relatively balanced level of spending control. Meanwhile, infrequent users tend to prefer cash payments due to financial control considerations, psychological comfort, and concerns related to technical and security aspects of digital transactions. Nevertheless, all respondents acknowledged that QRIS provides convenience and efficiency in daily transactions. This study concludes that QRIS usage influences the shopping behavior of FEB UGJ students, particularly in terms of shopping frequency, perceived convenience, and expenditure control. These findings highlight that the intensity of QRIS usage plays an important role in shaping students shopping patterns, indicating the need for financial awareness and literacy to ensure that QRIS is used wisely.